2001
DOI: 10.1002/nme.119
|View full text |Cite
|
Sign up to set email alerts
|

Sparse self‐stress matrices for the finite element force method

Abstract: SUMMARYA basic problem in the ÿnite element force method is that of obtaining a sparse and banded selfstress matrix and a sparse and banded structure exibility matrix. Traditionally the self-stress matrix is obtained through the application of algebraic procedures to the equilibrium matrix. The self-stress matrix for an indeterminate structure is not unique, and it is possible to obtain another self-stress matrix from an existing one through algebraic operations and grouping of redundants. The purpose of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 13 publications
(10 reference statements)
0
16
0
Order By: Relevance
“…There are also algebraic methods for the force method of structural analysis developed by Denke [9], Kaneko et al [10], Topçu [11], Soyer and Topçu [12]. The main advantage of these methods is their generality; however, graph theoretical methods are more efficient when applied to frame structures with no singularities.…”
Section: A Kaveh and R Mirzaiementioning
confidence: 99%
See 2 more Smart Citations
“…There are also algebraic methods for the force method of structural analysis developed by Denke [9], Kaneko et al [10], Topçu [11], Soyer and Topçu [12]. The main advantage of these methods is their generality; however, graph theoretical methods are more efficient when applied to frame structures with no singularities.…”
Section: A Kaveh and R Mirzaiementioning
confidence: 99%
“…It can be shown that the sum of two cycle set vectors of a graph is also a cycle set vector. Thus, the cycle set vectors of a graph form a vector space over the field of integer modulo 2 [12]. The dimension of a cycle space is equal to the first Betti number of the graph b 1 (S).…”
Section: Basic Definitions From Graph Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Algebraic methods have been developed by Denke [9], Robinson [10], Topçu [11], Kaneko et al [12] and Soyer and Topçu [13], and mixed algebraic-topological methods have been used by Gilbert and Heath [14], Coleman and Pothen [15,16], and Pothen [17]. Developments for use with finite element models (FEMs) based on hybrid equilibrium elements are due to Maunder [18] and Maunder and Savage [19].…”
Section: Introductionmentioning
confidence: 99%
“…Algebraic methods have been developed by Denke [9], Robinson [10], Topçu [11], Kaneko et al [12], Soyer and Topçu [13], and mixed algebraic-topological methods have been used by Gilbert and Heath [14], Coleman and Pothen [15,16] and Pothen [17]. The integrated force method has been developed by Patnaik [18,19], in which member forces are used as variables, and the equilibrium equations and the compatibility conditions are satisfied simultaneously in terms of these variables.…”
Section: Introductionmentioning
confidence: 99%